ChemInform Abstract: Further New Xenicanes from a Chinese Collection of the Brown Alga Dictyota plectens. Issue 16 (March 2016) - Zhao, Min; Cheng, Shimiao; Yuan, Weiping; Dong, Jianyong; Huang, Kexin; Sun, Zhongmin; Yan, Pengcheng
Abstract: Four new xenicanes (I)—(III) are isolated along with four known analogues and evaluated for their bioactivity.